Meaning of Gaze Behaviors in Individuals' Perception and Interpretation of Commercial Interior Environments: An Experimental Phenomenology Approach Involving Eye-Tracking - Kwon, Jain; Kim, Ju Yeon (Frontiers in Psychology, 2021)
A critical question in interior design is how multisensory information is integrated into occupant perception and interpretation of the environmental contexts and meanings. Although there have been efforts to identify and theorize visual perception of interior factors or features (e.g., colors, fixtures, and signs), the hidden meanings behind visual attention and behaviors have been neglected in interior design research. This experimental phenomenological study investigates the impact of auditory stimuli on individuals’ gaze behaviors and the hidden meanings of their audio-visual perceptions of commercial interiors. Implementing eye tracking and open-ended interview, this study explored how the neurophysiological and phenomenological methods in complementary can serve for interior design research on the meaning of gaze behaviors. The study used a convenience sample of 26 participants, three coffee shop interior images, and two musical stimuli. Essential to this study is the interpretive analysis of corresponding eye tracking and interview data. The results show that visual perception is affected by auditory stimuli and other interior elements and factors associated with personal experiences; however, no distinct gaze pattern is identified by the type of auditory stimuli. The fixation patterns showed mixed reflections of the participants’ perceptions, e.g., a single fixation pattern reflecting participants’ likes and dislikes. Findings included six essential meanings of participants’ gaze behaviors. This study suggests that auditory and visual stimuli are reciprocal in individuals’ perception, rather than one affects the other; the interaction between sensory stimuli contributes to the complexity and intensity of multisensory stimuli people associate with their experiences and conceptualize with meanings they establish.